The LPB1 Gene Is Important for Acclimation of Chlamydomonas reinhardtii to Phosphorus and Sulfur Deprivation - Chang, Chiung-Wen (American Society of Plant Biologists, 2005)
Organisms exhibit a diverse set of responses when exposed to low-phosphate conditions. Some of these responses are specific for phosphorus limitation, including responses that enable cells to efficiently scavenge phosphate from internal and external stores via the production of high-affinity phosphate transporters and the synthesis of intracellular and extracellular phosphatases. Other responses are general and occur under a number of different environmental stresses, helping coordinate cellular metabolism and cell division with the growth potential of the cell. In this article, we describe the isolation and characterization of a mutant of Chlamydomonas reinhardtii, low-phosphate bleaching (lpb1), which dies more rapidly than wild-type cells during phosphorus limitation. The responses of this mutant to nitrogen limitation appear normal, although the strain is also somewhat more sensitive than wild-type cells to sulfur deprivation. Interestingly, depriving the cells of both nutrients simultaneously allows for sustained survival that is similar to that observed with wild-type cells. Furthermore, upon phosphorus deprivation, the lpb1 mutant, like wild-type cells, exhibits increased levels of mRNA encoding the PHOX alkaline phosphatase, the PTB2 phosphate transporter, and the regulatory element PSR1. The mutant strain is also able to synthesize the extracellular alkaline phosphatase activity upon phosphorus deprivation and the arylsulfatase upon sulfur deprivation, suggesting that the specific responses to phosphorus and sulfur deprivation are normal. The LPB1 gene was tagged by insertion of the ARG7 gene, which facilitated its isolation and characterization. This gene encodes a protein with strong similarity to expressed proteins in Arabidopsis (Arabidopsis thaliana) and predicted proteins in Oryza sativa and Parachlamydia. A domain in the protein contains some similarity to the superfamily of nucleotide-diphospho-sugar transferases, and it is likely to be localized to the chloroplast or mitochondrion based on programs that predict subcellular localization. While the precise catalytic role and physiological function of the putative protein is not known, it may function in some aspect of polysaccharide metabolism and/or influence phosphorus metabolism (either structural or regulatory) in a way that is critical for allowing the cells to acclimate to nutrient limitation conditions.